Case report: Optimized ruxolitinib-based therapy in an infant with familial hemophagocytic lymphohistiocytosis type 3 - Niizato, Daiki; Isoda, Takeshi; Mitsuiki, Noriko; Kaneko, Shuya; Tomomasa, Dan; Kamiya, Takahiro; Takagi, Masatoshi; Imai, Kohsuke; Kajiwara, Michiko; Shimizu, Masaki; Morio, Tomohiro; Kanegane, Hirokazu (Frontiers in Immunology, 2022)
Familial hemophagocytic lymphohistiocytosis (FHL) is a rare and fatal autosomal recessive immune disorder characterized by uncontrolled activation of T and NK cells, macrophages, and overproduction of inflammatory cytokines. Early hematopoietic cell transplantation (HCT) is required for long-term survival. Current therapy is based on the HLH-94/2004 protocol, but is insufficient to fully control disease activity. This case report describes an infant with FHL type 3 who, despite initial therapy with dexamethasone and etoposide, showed aberrant cytokine levels, including interleukin-18 (IL-18), chemokine ligand 9 (CXCL9), soluble interleukin-2 receptor (sIL-2R), and soluble tumor necrosis factor receptor type II (sTNF-RII). The Janus kinase inhibitor ruxolitinib was therefore coadministered. The patient was treated with dose-adjusted ruxolitinib guided by cytokine profiles, and was successfully prepared for HCT. The results demonstrate the effectiveness and safety of dose-adjusted ruxolitinib as a bridging therapy for FHL, and the value of monitoring cytokine levels, especially IL-18, CXCL9, sIL-2R, and sTNF-RII, as disease-activity markers for FHL.